2021
DOI: 10.1080/21665095.2021.1950019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urban green spaces on the probability of urban crime in Indonesia

Abstract: Does the presence of green spaces in urban environments reduce the probability of crime? This paper applies the difference-in-differences approach to quantify the impact of urban green spaces on the probability of crime occurrence using data from the three largest metropolitan areas in Indonesia. Specifically, the study employs urban wards level data from the Village Potential Census (PODES) of 2014 and 2018 collected by Indonesia Statistics. Estimation results indicate a negative and significant impact of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Numerous studies conducted by various researchers also confirm that green spaces contribute to reducing the level of crime in cities. This is evidenced by studies carried out in diverse locations, including Toronto, Canada (Onifade, 2020), Brisbane, Australia (Kimpton et al, 2017), New Haven, USA (Gilstad-Hayden et al, 2015), Tehran, Iran (Ambrey and Shahni, 2017), metropolitan areas in Indonesia (Sukartini et al, 2021), and cities in South Africa (Venter et al, 2022).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Numerous studies conducted by various researchers also confirm that green spaces contribute to reducing the level of crime in cities. This is evidenced by studies carried out in diverse locations, including Toronto, Canada (Onifade, 2020), Brisbane, Australia (Kimpton et al, 2017), New Haven, USA (Gilstad-Hayden et al, 2015), Tehran, Iran (Ambrey and Shahni, 2017), metropolitan areas in Indonesia (Sukartini et al, 2021), and cities in South Africa (Venter et al, 2022).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Other studies have shown that green spaces in housing environment can be associated with increased survival in older populations and lower stroke mortality ( [33]; [19]). In other studies by [4]; [22]; [32] have identified an indirect benefits of urban green spaces in the reduction of crime in cities in the developed world. A sustainable environment needs to be protected as described by [3] and green environment propels sustainable environment.…”
Section: Importance Of Green Spaces In Residential Environmentsmentioning
confidence: 95%
“…In a study carried out by [32] in three largest metropolitan areas in Indonesia to know the effect of green space on the probability of crime occurrence, the study observed that with the reduction of green spaces in the studied area, there is an increase in crime. Findings from the study also argued against the common perception of relating urban green spaces with violence and crime.…”
Section: Environmental Security With Green Spaces In Public Housingmentioning
confidence: 99%
“…Potential criminals could interpret this in the same way and consider these conditions to be inhibiting the opportunity to commit a crime. In a study in Indonesia using data provided by urban wards (municipal administrative divisions), Sukartini et al (2021) found that an increase in greenspace resulted in less crime and a decrease in greenspace resulted in more crime. Several studies have been published on the impact of greening blighted vacant lots.…”
Section: Greenspace and Crime Reductionmentioning
confidence: 99%